The Cultural Production of Intellectual Property Rights - Johnson Andrews, Sean (Temple University Press, 2019)
This book looks at questions of intellectual property rights (IPR) -- historically, culturally, and politically -- and their relationship to law and the state. Arguing that the idea that intellectual property is another kind of property right (that is, that IP is a thing to be owned) exists in parallel with the idea that intellectual property is the consequence of a cultural process, Andrews discusses intellectual property rights within the context of cultural studies, treating them as an object through which intersecting cultural and political issues can be understood.